EXPERIENCE REPORT: ADMISSION TO THE UNIVERSITY WITH REMOTE EDUCATION - Samuel Laurindo de Lima, Francisco (Revista Gênero e Interdisciplinaridade, 2023)
It appears that remote teaching at the university generated social distancing (physically) and made it impossible for many to access the new teaching model, due to several students not having internet and/or devices available. Therefore, the purpose of this educational work is to report the problems and solutions that affected virtual learning, through the experiences of the student Francisco Samuel Laurindo de Lima (graduating in Pedagogy at UECE-Tauá/CE) during the first semester. This educational research points out details covered in the entrance to the college in focus, linked to the non-face-to-face space, with respective theoretical research methods and analysis of online classes. Positive results are observed (development in oratory and writing for requested activities, and excellent use in virtual surveys, etc.), after using qualitative methodologies. Well, they are important to acquire good conclusions about the a analyzed, and they indicate that it is necessary the educational praxis with commitment related to the teaching during any situations, mainly more in the strong adversities, example; COVID-19 pandemic, to acquire advantages. In this way, it will contribute to a “jaez” education, that is, a pragmatic educational progress, which in this sense, arises in the first place from the good actions of students and teachers.